Indices of resting metabolic rate accurately reflect energy deficiency in exercising women - Strock, N. C. A.; Koltun, K. J.; Southmayd, E. A.; Williams, N. I.; de Souza, M. J. (International Journal of Sport Nutrition and Exercise Metabolism, 2020)
Energy deficiency in exercising women is associated with severe consequences including reproductive dysfunction (De Souza et al., 2007b; Williams et al., 2015) and impaired bone health (De Souza et al., 2008), a condition referred to as the Female Athlete Triad (Triad) (De Souza et al., 2014; Nattiv et al., 2007). When energy intake fails to meet metabolic demands, metabolizable fuels are repartitioned toward the physiological processes necessary for survival (i.e., locomotion, cellular maintenance, and thermoregulation) and away from those energetic processes deemed unnecessary for survival (i.e., growth and reproduction). This results in suppression of metabolism, energy expenditure, and thyroid hormones (Wade et al., 1996), contributing to the development of exercise-associated menstrual disturbances (Loucks et al., 1998). Exercise-associated menstrual disturbances can range in severity from luteal phase defects to amenorrhea consistent with the magnitude of energy deficiency, such that those with the most severe menstrual disturbances are also the most energy deficient (De Souza et al., 2007b). Owing to the long-term health outcomes associated with energy deficiency (De Souza et al., 2007b, 2008; Williams et al., 2015), early intervention and prevention are necessary.